2015
DOI: 10.1189/jlb.3a1214-620rr
|View full text |Cite
|
Sign up to set email alerts
|

Expression and role of a2 vacuolar-ATPase (a2V) in trafficking of human neutrophil granules and exocytosis

Abstract: Neutrophils kill microorganisms by inducing exocytosis of granules with antibacterial properties. Four isoforms of the "a" subunit of V-ATPase-a1V, a2V, a3V, and a4V-have been identified. a2V is expressed in white blood cells, that is, on the surface of monocytes or activated lymphocytes. Neutrophil associated-a2V was found on membranes of primary (azurophilic) granules and less often on secondary (specific) granules, tertiary (gelatinase granules), and secretory vesicles. However, it was not found on the surf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 59 publications
0
9
0
Order By: Relevance
“…Stimulated cells were also examined by flow cytometry. When mast cells are stimulated, the release of granular content results in the exposure of phosphatidylserine on the external surface of the cell, which can be quantified by FITC-annexin V staining [33,34]. For RBL-2H3 cells, a P4 gate was set on resting cells that included 95% of cells and a P5 gate on stimulated cell that included 95% of cells not in P4 ( Fig.…”
Section: Effect Of Rho Drugs On Mast Cell Degranulationmentioning
confidence: 99%
“…Stimulated cells were also examined by flow cytometry. When mast cells are stimulated, the release of granular content results in the exposure of phosphatidylserine on the external surface of the cell, which can be quantified by FITC-annexin V staining [33,34]. For RBL-2H3 cells, a P4 gate was set on resting cells that included 95% of cells and a P5 gate on stimulated cell that included 95% of cells not in P4 ( Fig.…”
Section: Effect Of Rho Drugs On Mast Cell Degranulationmentioning
confidence: 99%
“…Following these findings, it was further demonstrated that a 2V deficiency in tumor cells alters the resident macrophage population in the tumor microenvironment and affects in vivo tumor growth [ 34 ]. a 2V is expressed on the primary granules of neutrophils and helps maintain pH in exocytic pathway during neutrophil activation [ 35 ]. Treatment of human neutrophils with recombinant N terminal peptide of a2V (a2NTD) promoted neutrophil migration and polarization [ 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…The fact that Tg197/Tg5519 inflamed ankles overexpress various V-ATPase subunits either osteoclast specific such as ATP6V1B2, and TCIRG1 or ubiquitous ATP6V1A, ATP6V1E1, and ATPV0D1 indicates an overwhelming osteoclastic activity that causes massive joint destruction, which is also confirmed by the histological analysis. Upregulated V-ATPase subunits could also have an impact on inflammatory responses such as phagocytosis, cytokine secretion and exocytosis of neutrophil granules (57, 58). Notably, recent studies have shown that in inflammatory conditions, osteoclasts can differentiate from dendritic cells in the presence of RANKL and behave as antigen-presenting cells (59).…”
Section: Discussionmentioning
confidence: 99%